Discovery-Project-Evaluation-STEM model: A promising learning model for Bima local cultural character - Landa, Sudarsono; Mawaddah, Ida (Journal of Honai Math, 2024)
An effective learning model that actively involves students in the learning process is essential. This development research aims to identify the factors responsible for the observed low problem-solving ability in geometry and to develop a model that effectively enhances these skills. The research process begins with the creation of flow diagrams using the ADDIE model, encompassing the analysis, design, development, implementation, and evaluation phases. The study focuses on junior high school students. The research findings, which consider the unique cultural characteristics of the Bima people, suggest that the Discovery-Project-Evaluation (DPjE) learning model, incorporating STEM elements, can be an effective alternative or complement to traditional teaching methods. Six experts confirmed that the geometric problem-solving skills test instrument outperformed other learning tools. Data from limited trials indicate that using lesson plans and worksheets, along with positive feedback from educators and students, supports the effectiveness of the developed learning materials. This demonstrates the practical application of the DPjE model, with STEM elements based on Bima Local Cultural Character (BLCC), in teaching mathematics. The BLCC-based DPjE-STEM model assesses the learning process's efficiency using data from initial and final tests.